2003
DOI: 10.1029/2002gl016563
|View full text |Cite
|
Sign up to set email alerts
|

The transformation of solid atmospheric particles into liquid droplets through heterogeneous chemistry: Laboratory insights into the processing of calcium containing mineral dust aerosol in the troposphere

Abstract: [1] Individual calcium carbonate particles reacted with gas-phase nitric acid at 293 K have been followed using Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray (EDX) analysis as a function of time and relative humidity (RH). The rate of calcium carbonate to calcium nitrate conversion is significantly enhanced in the presence of water vapor. The SEM images clearly show that solid CaCO 3 particles are converted to spherical droplets as the reaction proceeds. The process occurs through a two-step m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
141
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(156 citation statements)
references
References 15 publications
14
141
1
Order By: Relevance
“…Several field studies have indicated that mineral dust particles, through heterogeneous uptake of acidic gases, acquire coatings of sulfates (Kojima et al, 2006;Sullivan et al, 2007), and/or nitrates (Zhang et al, 2000;Laskin et al, 2005a;Matsuki et al, 2005;Hwang and Ro, 2006). Although laboratory studies provided detailed information regarding nitrate coatings formed through heterogeneous reactions (Krueger et al, 2003(Krueger et al, , 2004Laskin et al, 2005b), few studies present data on nitrate coatings detected in ambient particles.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several field studies have indicated that mineral dust particles, through heterogeneous uptake of acidic gases, acquire coatings of sulfates (Kojima et al, 2006;Sullivan et al, 2007), and/or nitrates (Zhang et al, 2000;Laskin et al, 2005a;Matsuki et al, 2005;Hwang and Ro, 2006). Although laboratory studies provided detailed information regarding nitrate coatings formed through heterogeneous reactions (Krueger et al, 2003(Krueger et al, , 2004Laskin et al, 2005b), few studies present data on nitrate coatings detected in ambient particles.…”
Section: Introductionmentioning
confidence: 96%
“…When aged by soluble aerosol components, these mineral particles will have enhanced hygroscopicity and altered sizes and shapes (Krueger et al, 2003(Krueger et al, , 2004Laskin et al, 2005b). As a result, the coated dust particles become more efficient CCN (Kelly et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the Ca-rich particles collected on the reactive nitron reagent film, At least 60% up to 90% of the Carich particles on the reactive nitron reagent film contained NO − 3 . It becomes evident that mineral dust particles enriched in carbonate minerals such as calcite (CaCO 3 ) and dolomite (MgCa(CO 3 ) 2 ) react with HNO 3 gas to form extremely hygroscopic Ca(NO 3 ) 2 or Mg(NO 3 ) 2 which are suggested to readily deliquesce under subsaturated atmospheric conditions (Krueger et al, 2003(Krueger et al, , 2004Laskin et al, 2005;Matsuki et al, 2005b). Although carbonate minerals are reported to comprise significant fraction of the atmospheric irregular dust particles in many parts of the globe (Ganor and Mamane, 1982;Okada and Kai, 1995; 2004; Kandler et al, 2007), irregularly shaped Ca-rich particles were hardly found in this study.…”
Section: Morphology and Compositionmentioning
confidence: 99%
“…In addition, the chemical aging of dust particles (e.g. formation of particulate nitrate and/or sulphate) (Laskin et al, 2005;Matsuki et al, 2005;Mori et al, 2003;Sullivan et al, 2007) can modify their hygroscopicity and ability to serve as cloud condensation nuclei (Krueger et al, 2003;Shi et al, 2008;Sullivan et al, 2009;Tobo et al, 2010). Finally, heterogeneous processing can influence the ice nucleation properties of mineral dust particles (Cziczo et al, 2009;Kanji et al, 2013;Niedermeier et al, 2010;Sullivan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%